Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1063/1.4940344
|View full text |Cite
|
Sign up to set email alerts
|

Features of the electronic structure of the ternary superconductors RRh4B4 (R = Y, Lu)

Abstract: The electronic structure and a number of thermodynamic characteristics of the ternary RRh4B4 (R = Y, Lu) systems of superconductors in the normal phase are calculated from first principles. The electronic states and interactions responsible for the superconducting and magnetic properties of these systems are analyzed. It is found that the Fermi level in the compounds YRh4B4 and LuRh4B4 is immediately adjacent to a peak in the density of electronic states and about 1 eV above a pseudogap in the electronic spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Because Ru substitution for Rh controls the interatomic distances between borons and between boron and Rh/Ru atoms, the density of states at Fermi energy is tuned by doping, leading to a change in T c . The electronic structure of YRh 4 B 4 has been calculated using the full potential relativistic linear muffin-tin orbital (LMTO) method considering the exchange-correlation potential in terms of the local density approximation of the density functional theory by Grechnev et al [9]. The calculation of density of states revealed that a pseudogap opens approximately 1 eV below the Fermi energy level.…”
Section: Introductionmentioning
confidence: 99%
“…Because Ru substitution for Rh controls the interatomic distances between borons and between boron and Rh/Ru atoms, the density of states at Fermi energy is tuned by doping, leading to a change in T c . The electronic structure of YRh 4 B 4 has been calculated using the full potential relativistic linear muffin-tin orbital (LMTO) method considering the exchange-correlation potential in terms of the local density approximation of the density functional theory by Grechnev et al [9]. The calculation of density of states revealed that a pseudogap opens approximately 1 eV below the Fermi energy level.…”
Section: Introductionmentioning
confidence: 99%